2011
DOI: 10.1007/s12040-011-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Elastic thickness estimates at northeast passive margin of North America and its implications

Abstract: Global estimates of the elastic thickness (Te) of the structure of passive continental margins show wide and varying results owing to the use of different methodologies. Earlier estimates of the elastic thickness of the North Atlantic passive continental margins that used flexural modelling yielded a Te value of ∼20-100 km. Here, we compare these estimates with the Te value obtained using orthonormalized Hermite multitaper recovered isostatic coherence functions. We discuss how Te is correlated with heat flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…They iteratively compared the calculated gravity anomaly to the observed free-air gravity anomaly to derive a best-fit Te structure that shows a significant variation of 0 b Te b 40 km, which they attributed to strength variation in the rifted lithosphere. Several studies revealed crustal thinning and depth of necking as appropriate parameters to predict the flexural response of lithospheric stretching (Braun and Beaumont, 1989;Fourno and Roussel, 1994;Ratheesh Kumar et al, 2011). Ratheesh used the orthonormalized Hermite multitaper method to estimate Te along the northeastern passive margin of North America, and suggested that low-Te values were indicative of the passive nature of the margin when loads were emplaced during the continental break-up process at hightemperature gradients.…”
Section: Introductionmentioning
confidence: 99%
“…They iteratively compared the calculated gravity anomaly to the observed free-air gravity anomaly to derive a best-fit Te structure that shows a significant variation of 0 b Te b 40 km, which they attributed to strength variation in the rifted lithosphere. Several studies revealed crustal thinning and depth of necking as appropriate parameters to predict the flexural response of lithospheric stretching (Braun and Beaumont, 1989;Fourno and Roussel, 1994;Ratheesh Kumar et al, 2011). Ratheesh used the orthonormalized Hermite multitaper method to estimate Te along the northeastern passive margin of North America, and suggested that low-Te values were indicative of the passive nature of the margin when loads were emplaced during the continental break-up process at hightemperature gradients.…”
Section: Introductionmentioning
confidence: 99%
“…The total equivalent topography ( Fig. 4), defined as the height or depth that the crust will assume in the absence of water and under isostatic conditions (Kumar et al, 2011), is calculated with equation 4.…”
Section: Flexural Modelingmentioning
confidence: 99%